Use of AI Chatbots among Librarians: Implications for Future Library Services - Arumuru, Lawrence (International Journal of Information Studies, 2025)
The purpose of this study was to examine the use of AI chatbots among librarians in Nigerian university libraries and assess their potential impact on future library services. The study was conducted to investigate the current usage levels of AI chatbots, their potential for enhancing service delivery in the future, and the challenges associated with their implementation. Guided by the Technology Acceptance Model, an ex post facto research design was employed. Data were collected through a questionnaire distributed to a purposive sample of 278 librarians (28%) from a population of 989 across six states in Nigeria’s geopolitical zones. Of the distributed questionnaires, 200 responses (72%) were completed and analyzed using descriptive statistics, including frequency, percentage, and mean. The criterion mean of 2.50 was established for interpreting the data, with findings indicating a low current usage level of AI chatbots among librarians (Aggregate x = 1.92, Crit. x = 2.50).The study revealed promising prospects for AI chatbots in Nigerian university libraries, including their potential to significantly automate routine tasks (91%), improve accessibility to library resources (81%), enhance outreach programs (76%), provide multilingual support (71%), offer personalized user support (66%), and support research activities (65%). However, several challenges were identified, such as difficulties in customizing AI chatbots for specific library needs (96%), issues with user acceptance and trust (94%), limitations in handling specific topics (86%), the need for regular software updates (85%), and concerns regarding privacy and security (80%). The study recommends that university administrators and library leaders invest in modern technological infrastructure and provide comprehensive training for librarians to ensure effective implementation and management of AI systems. Addressing these challenges and capitalizing on the potential of AI chatbots could transform future library services in Nigerian universities.